Pengaruh Variasi Temperature Pengeringan Powder Coating Terhadap Daya Rekat Lapisan Cat Pada Mild Steel ST37 - Dzaky Al Dzikri; Ratna Dewi Anjani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Painting with the powder coating method is still rarely found because the price is expensive and also the process is quite long. Most of the use of this method is for painting motorcycle frames, trellis fences to truck bumpers. The properties of powder coating itself are better than liquid coating because it goes through a drying process using an oven so that its durability can be longer and difficult to scratch. The purpose of this research is to find out at which temperature and pretreatment the adhesion of the paint layer on the specimen gets the best results, also see how much corrosion rate occurs in each test specimen. The method used is experimental and through two different pretreatment stages before painting. The results showed that the adhesion test received a classification of 0B-2B or the peeled paint layer was 35% - 100% at a temperature of 140˚C in both pretreatment methods and at a temperature of 180˚C with the dry pretreatment method received a classification of 2B or the peeled paint layer was 15% - 35% and the phospating pretreatment method received a classification of 5B. While at the maximum temperature at 220˚C both pretreatments received a classification of 5B or no paint layers peeled off from the surface of the test specimen. This indicates that at a drying temperature of 180˚C the phospating pretreatment method has obtained maximum results compared to dry pretreatment.